Bacillus megaterium WL-3 Lipopeptides Collaborate Against Phytophthora infestans to Control Potato Late Blight and Promote Potato Plant Growth - Wang, Youyou; Liang, Jiao; Zhang, Congying; Wang, Le; Gao, Wenbin; Jiang, Jizhi (Frontiers in Microbiology, 2020)
Oomycete Phytophthora infestans ((Mont.) de Bary) is the cause of potato late blight, a plant disease which poses a serious threat to our global food security and is responsible for huge economic losses worldwide. Lipopeptides produced by Bacillus species are known to be potent antibacterial compounds against many plant pathogens. In this study, we show that Bacillus megaterium WL-3 has an antagonistic effect against potato late blight. Electrospray ionization mass spectrometry (ESI-MS) revealed that lipopeptides derived from the WL-3 strain contained three subfamilies, surfactin (C13 - C15), Iturin A (C14 - C16), and Fengycin A (C15 - C19). The Iturin A and Fengycin A lipopeptide families were each confirmed to have anti-oomycete effects against P. infestans mycelium growth as well as obvious controlling effects against potato late blight in greenhouse experiments and field assays. Furthermore, Iturin A and Fengycin A were able to promote plant photosynthetic efficiency, plant growth, and potato yield. Most importantly, the combination of Iturin A and Fengycin A (I + F) was superior to individual lipopeptides in controlling potato late blight and in the promotion of plant growth. The results of this study indicate that B. megaterium WL-3 and its lipopeptides are potential candidates for the control of late blight and the promotion of potato plant growth.